2005
DOI: 10.1007/s10530-004-9635-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an introduced Crustacean on the trophic webs of Mediterranean wetlands

Abstract: Based on a review and our own data, we present an overview of the ecological impacts on the trophic web of Mediterranean wetlands by an introduced Decapod Crustacean, the red swamp crayfish (Procambarus clarkii). P. clarkii lacks efficient dispersal mechanisms but is very well adapted to the ecological conditions of Mediterranean wetlands (fluctuating hydroperiods with regular intervals of drought). As an opportunistic, omnivorous species, which adapts its ecology and life history characteristics, such as timi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(136 citation statements)
references
References 92 publications
3
127
3
3
Order By: Relevance
“…The highly aggressive behavior, potential for rapid population increase, and omnivorous feeding habits of P. clarkii have resulted in numerous ecological impacts manifested across entire lake food webs (e.g., Geiger et al 2005;Gherardi 2006; Gherardi and Acquistapace 2007). P. clarkii was first recorded in Washington in the summer of 2000 (Mueller 2001).…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly aggressive behavior, potential for rapid population increase, and omnivorous feeding habits of P. clarkii have resulted in numerous ecological impacts manifested across entire lake food webs (e.g., Geiger et al 2005;Gherardi 2006; Gherardi and Acquistapace 2007). P. clarkii was first recorded in Washington in the summer of 2000 (Mueller 2001).…”
Section: Study Speciesmentioning
confidence: 99%
“…Crayfish are important polytrophic consumers in temperate freshwater environments and play a central ecological role by providing a direct link from primary production and detrital-based food webs to fish and terrestrial predators (Nyström et al 1996). Small-scale experiments and field studies have demonstrated significant ecological impacts of P. clarkii and O. virilis on detritus, macrophytes, benthic insects, snails, crayfishes and fish in lotic and lentic waters (e.g., Chambers et al 1990;Geiger et al 2005;Gherardi 2006;Gherardi and Acquistapace 2007). These species have only recently been documented in Washington (Mueller 2001;Larson and Olden 2008) and are invading a freshwater landscape occupied by a single native crayfish species-the signal crayfish (Pacifastacus leniusculus) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This generalization of detection capability to novel predator species, however, gets dampened with increasing phylogenetic distance among predator species [28], and no indigenous crayfish species have been known in the Doñ ana area. The red swamp crayfish was introduced in the surroundings of Doñ ana National Park in 1974, and it has since unevenly expanded across marshy areas and into ponds throughout the park [29], although it has not reached the southernmost part of the park. Rana perezi is widely extended throughout the park, including a number of isolated ponds to the south that remain free of invasive crayfish.…”
Section: Introductionmentioning
confidence: 99%
“…This type of indirect interaction is also similar to ''hyperpredation'' when the shared predator is an exotic species (Smith and Quin 1996). Hyperpredation is a notorious mechanism causing severe declines and even extinctions of native species (Norbury 2001;Roemer et al 2002;Courchamp et al 2003;White et al 2006), and this mechanism may explain why exotic red swamp crayfish have large impacts on native ecosystems (Maezono and Miyashita 2004;Geiger et al 2005;Gherardi and Acquistapace 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Here, we focused on the red swamp crayfish which is a notorious invasive species introduced worldwide, reducing the abundance of aquatic macrophytes and insects (Holdich et al 1988;Maezono and Miyashita 2004;Geiger et al 2005;Gherardi and Acquistapace 2007). In Japan, the red swamp crayfish was introduced approximately 80 years ago and is now established widely in freshwater ecosystems (Ban 1980).…”
Section: Introductionmentioning
confidence: 99%